Linking Classroom to Real-World Practices: Problem-Based Learning in Microteaching for EFL Teaching Practicum Preparation - Willy Prasetya; Anandayu Suri Ardini (IJELR: International Journal of Education, Language, and Religion, 2023)
Although Problem-Based Learning has been frequently explored in higher education, little is known about how it is implemented in English teaching practicum preparation context. To fill this practical gap, this article discusses the implementation of Problem-Based Learning in a microteaching class to prepare EFL pre-service teachers for teaching practicum in schools with various conditions. This article elaborates how students critically identified and found solution to the authentic problems posed at the beginning of every practicum cycle. This problem-solving process not only developed pre-service teachers’ critical thinking but also raised their awareness of the importance of being an adaptive teacher.